1999
DOI: 10.1165/ajrcmb.21.1.3542
|View full text |Cite
|
Sign up to set email alerts
|

β -Hexosaminidase–Induced Activation of p44/42 Mitogen-Activated Protein Kinase Is Dependent on p21Ras and Protein Kinase C and Mediates Bovine Airway Smooth-Muscle Proliferation

Abstract: Late-phase and sustained activation of p44/42(MAPK) has been reported to be a critical factor in cell mitogenesis. We therefore hypothesized that p44/42(MAPK) is involved in mannosyl-rich glycoprotein-induced mitogenesis in bovine airway smooth-muscle cells (ASMC). Treatment of adherent ASMC with beta-hexosaminidase A (Hex A, 50 nM), an endogenous mannosyl-rich glycoprotein, resulted in a late-onset (30-min) activation of p44/42(MAPK) that lasted for 4 h. Activation of p44/42(MAPK) induced by Hex A was inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 41 publications
1
16
0
1
Order By: Relevance
“…Zdaniem Lewa i wsp. [13] HEX A działający na kwaśne substraty, takie jak glikozoaminoglikany i glikolipidy oraz glikoproteiny zawierające kwasy sialowe, jest mediatorem stanu zapalnego wydzielanym do przestrzeni zewnątrz-komórkowej, odzwierciedla w płynach ustrojowych aktywność metaboliczną i wydzielniczą komórek. HEX B działający na obojętne łańcuchy oligosacharydowe jest wskaźnikiem uszkodzenia komórek [13].…”
Section: The Activity Of Hex and Its Isoenzymes A (Hex A) And B (Heunclassified
“…Zdaniem Lewa i wsp. [13] HEX A działający na kwaśne substraty, takie jak glikozoaminoglikany i glikolipidy oraz glikoproteiny zawierające kwasy sialowe, jest mediatorem stanu zapalnego wydzielanym do przestrzeni zewnątrz-komórkowej, odzwierciedla w płynach ustrojowych aktywność metaboliczną i wydzielniczą komórek. HEX B działający na obojętne łańcuchy oligosacharydowe jest wskaźnikiem uszkodzenia komórek [13].…”
Section: The Activity Of Hex and Its Isoenzymes A (Hex A) And B (Heunclassified
“…Finally, LEW et al [104] have demonstrated that induction of proliferation in bovine tracheal smooth muscle by bhexosaminidase and activation of the ERK pathway is prevented by the PKC inhibitor calphostin C, an effect which appears to be mediated at the Ras/Raf-1 locus ( fig. 3) [128].…”
Section: Interaction Of Protein Kinase C With Other Signalling Molecumentioning
confidence: 99%
“…The derivatized sample was then injected onto a C ") reverse-phase column (Shodex C ") , 5 µm spherical particles, 4.6 mm internal diam.i25 cm) equilibrated in solvent A at 43 mC, and eluted at a flow rate of 1. Airway smooth-muscle cell culture Primary cultures of bovine tracheal smooth-muscle cells were prepared from bovine trachealis muscle, as described previously [21]. Direct immunofluorescence staining of the cells with an FITC-conjugated monoclonal antibody against smooth-muscle isoactin (Sigma) demonstrated that cultures consisted of a homogeneous population of smooth-muscle cells [22].…”
Section: Hplc Analysis Of Methylated Amino Acidsmentioning
confidence: 99%
“…After a 48 h starvation, the inhibitors to be tested were added 30 min before stimulation of the cells. Without a change of medium, purified hexosaminidase A (Hex A) or vehicle (PBS) was added [21]. In some experiments, an agonistic antibody (mAb "& ; [23]) directed to the extracellular domain of human macrophage mannose receptors was used to stimulate cells.…”
Section: Assesment Of Proliferationmentioning
confidence: 99%
See 1 more Smart Citation